Digital NHS Wales: a coding reliability analysis based on the voices of 22 978 patients and clinicians on the benefits, challenges and sustainability of video consulting. Issue 4 (20th April 2022) - Johns, Gemma; Whistance, Bethan; Khalil, Sara; Whistance, Megan; Thomas, Bronwen; Ogonovsky, Mike; Ahuja, Alka
Abstract : Introduction: The use of video consulting (VC) in Wales UK has expanded rapidly. Previous VC evidence has been the subject of small-scale projects and evaluations. Technology Enabled Care Cymru is an all-Wales digital service and rolls out digital interventions and evaluates on large scales, thus capturing representative data sets across Wales, and therefore a wide range of National Health Service (NHS) specialties. Objective: To extract and analyse narrative feedback from patients and clinicians using the NHS Wales VC Service for 6 months (September 2020 to March 2021). Design: A coding reliability approach of a cross-sectional study was conducted. Setting: From all health boards across Wales. Participants: NHS patients and clinicians across primary, secondary and community care settings in Wales. Results: Data were captured on benefits, challenges and sustainability of VC. A coding reliability analysis was used with six domain summaries materialising to include: 'The Ease of VC'; 'The Personal Touches'; 'The Benefits of VC'; 'The Challenges of VC'; 'Technical Quality'; and 'Recommendations & Future Use'. An additional 17 subdomains are included. Direct quotations from patients and clinicians are provided for context. Conclusions: A total of 22 978 participants were included. These data help demonstrate that NHS remote service delivery, via the method of VC, can be highly satisfactory, well accepted and clinically suitable yielding many benefits. Despite this, the data are not without its challenges surrounding engagement and suitability for VC. The NHS Wales VC Service rolled out and evaluated at scale and demonstrates that VC has potential for long-term sustainability. For the future, use a 'blended approach' for NHS appointments that are clinically judged and centred on patient choice.